Pengaruh Harga dan Promosi Terhadap Minat Beli Konsumen Pada Restoran Taco Bell di Artha Gading Jakarta Utara - Syarif Hidayatullah; Syahrul Reza (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This research aims to determine the price and promotion of puechase decision at the Taco Bell restaurant in Artha Gading, North Jakarta. The population used in this research were consumers from Taco Bell with a total of 100 respondents. The method used in this research is multiple linear regression analysis. The research data was processed using Microsoft Excel and SPSS 20 software. The independent variables in this study were Price (X1) Promotion (X2). The dependent variable in this study is Purchase Decision (Y). The results of multiple linear regression analysis are, Y = 3.702 + 0.663 (X1) + 0.520 (X2) + e. The independent variables that have the most influence on the dependent variable are Price (0.663), Promotion (0.520). The results of the t test show that Price and Promotion have a positive and significant effect on Purchase Intention. The coefficient of determination obtained from the independent variables in this study is 83.1%. Meanwhile the remaining 17.9% is influenced by other variables outside this research.